Speech and brain-mechanisms - Penfield, Wilder, 1891-1976; Roberts, Lamar (Princeton, New Jersey : Princeton University Press, 1959)
The outcome of ten years' work, this book is a carefully planned study of brain dominance, aphasia, and other speech disturbances, and includes a discussion of the cerebral mechanisms of speech and the learning and teaching of language. Originally published in 1981. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These paperback editions preserve the original texts of these important books while presenting them in durable paperback e.
Cover; Vanuxem Lecturers; Preamble To The Vanuxem Lectures (W.P); Contents; V. Methode of Investingation; A. Special study; B. The Sodium Amytal Aphasia Test; C. Disturbances in Speech With Seizures; VI. Methods of Investigation (L.R.); A. Literature; B. Analysis of Our Cases; C. Discussion; D. Summary; IX. The Evidence From Cortical Excision (L.R.); X. Concluding Discussion (W.P.); E. Brain-Mechanisms of Language.
"The general conclusions embodied in this monograph were presented by Wilder Penfield in the Vanuxem lectures at Princeton University in February, 1956."
Includes bibliographical references.
Print version record.
eBooks on EBSCOhost
Keywords: Brain -- Localization of functions; Speech; Speech disorders; Speeches, addresses, etc; Brain Mapping; Speech; Speech Disorders; Localisation cérébrale.; Parole; Troubles de la parole; Discours; speeches (documents); speeches (compositions); speech (communication function); MEDICAL -- Physiology; SCIENCE -- Life Sciences -- Human Anatomy & Physiology; MEDICAL -- General; Brain -- Localization of functions; Speech; Speech disorders